Dosimetric comparison of Synchrony® real-time motion tracking treatment plans between CyberKnife robotic radiosurgery and Radixact system for stereotactic body radiation therapy of lung and prostate cancer. (21st April 2023) - Kong, C.W.; Chiu, T.L.; Geng, H.; Lam, W.W.; Yang, B.; Cheung, C.W.; Yu, S.K.
Abstract: The aim of this study was to assess which machine, Radixact or CyberKnife, can deliver better treatment for lung and prostate stereotactic body radiation therapy (SBRT) with the use of Synchrony® real-time motion tracking system. Ten and eight patients treated with lung and prostate SBRT, respectively, using the CyberKnife system were selected for the assessment. For each patient, a retrospective Radixact plan was created and compared with the original CyberKnife plan. There was no statistically significant difference in the new conformity index of the Radixact plans and that of the Cyberknife plans in both lung and prostate SBRT. The average homogeneity index in the Radixact plans was better in both lung and prostate SBRT with statistical significance ( p = 0·04 for lung and p = 0·02 for prostate). In lung SBRT, the dose to lungs was lower in Cyberknife plans ( p = 0·002). In prostate SBRT, there was no statistically significant difference in organs at risk sparing between Cyberknife plans and Radixact plans. In conclusion, CyberKnife was better in lung SBRT while Radixact was better in prostate SBRT.